Metagenomic Analysis of Flaviviridae in Mosquito Viromes Isolated From Yunnan Province in China Reveals Genes From Dengue and Zika Viruses - Xiao, Pengpeng; Han, Jicheng; Zhang, Ying; Li, Chenghui; Guo, Xiaofang; Wen, Shubo; Tian, Mingyao; Li, Yiquan; Wang, Maopeng; Liu, Hao; Ren, Jingqiang; Zhou, Hongning; et al. (Frontiers in Cellular and Infection Microbiology, 2018)
More than 6000 mosquitoes of six species from six sites were collected and tested for their virome using metagenomics sequencing and bioinformatic analysis. The identified viral sequences belonged to more than 50 viral families. The results were verified by PCR of selected viruses in all mosquitoes, followed by phylogenetic analysis. In the present study, we identified partial dengue virus (DENV), zika virus (ZIKV), and Japanese encephalitis virus (JEV) sequences in mosquitoes. Metagenomic analysis and PCR amplification revealed three DENV sequences, one of which encodes a partial envelope protein. Two ZIKV sequences both encoding partial nonstructural protein 3 and one JEV sequence encoding the complete envelope protein were identified. There was variability in viral titers of newly isolated virus JEV-China/YN2016-1 of different passage viruses. The newly identified zika virus gene from ZIKV-China/YN2016-1 was an Asian genotype and shared the highest nucleotide sequence identity (97.1%) with a ZIKV sequence from Thailand isolated in 2004. Phylogenetic analysis of ZIKV-China/YN2016-1 and ZIKV-China/YN2016-2 with known Flavivirus genes indicated that ZIKV has propagated in Yunnan province, China.